Analysis, Design and Fabrication of Micromixers - Kim, Kwang-Yong (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book includes an editorial and 12 research papers on micromixers collected from the Special Issue published in Micromachines. The topics of the papers are focused on the design of micromixers, their fabrication, and their analysis. Some of them proposed novel micromixer designs. Most of them deal with passive micromixers, but two papers report studies on electrokinetic micromixers. Fully three-dimensional (3D) micromixers were investigated in some cases. One of the papers applied optimization techniques to the design of a 3D micromixer. A review paper is also included and reports a review of recently developed passive micromixers and a comparative analysis of 10 typical micromixers.